Superior growth performance in carp fry achieved with chitosan-alginate encapsulated A-ghrelin versus free peptide: Evidence from physiological, molecular, and morphological analyses - Mohammad Matinfar; Behrooz Heidari; AbdolMajid Valipour; Tahereh Rahdari; Sorour Ramezanpour; Mahvash Hadavi; S. Mohsen Asghari (PLoS ONE, 2025)
This study investigates the potential of delivering ghrelin via chitosan-alginate (Cs-Al) nanocapsules to enhance growth performance, immune function, and stress biomarker parameters in common carp fry (Cyprinus carpio). Characterization of the nanoparticles revealed an average size of 130 nm for Cs-Al particles and 150 nm for A-ghrelin-loaded nanoparticles, with polydispersity indices (PDI) of 0.3 and 0.4, respectively. The zeta potential was measured at +20 mV for Cs-Al nanoparticles and +22 mV for ghrelin-loaded nanoparticles. Morphological analysis using FE-SEM and AFM revealed that the nanoparticles exhibit a predominantly spherical and uniform morphology, while FTIR analysis confirmed their successful synthesis and functionalization. The A-Ghrelin-Cs-Al NP group showed superior growth performance, with higher weight gain vs. control (P < 0.05) and thicker intestinal walls (P < 0.05). While all ghrelin treatments elevated IGF-1 expression (P < 0.05 vs. control), the Cs-Al NP delivery system reduced IgM levels (P < 0.05) and C3 (P < 0.05) compared to free A-Ghrelin, suggesting encapsulation may modulate immune responses. No significant differences in gill morphology were observed between groups (P > 0.05). These findings highlight the potential of ghrelin, particularly when delivered through alginate-chitosan nanocapsules, as a promising tool to promote growth and physiological health in juvenile fish. This approach offers a novel strategy to enhance aquaculture productivity and sustainability through nanotechnology-based delivery systems.